Kuznets' tension in India: Two episodes - Saon Ray; Sabyasachi Kar (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Developing countries face a trade-off between the twin objectives of structural transformation and inclusive growth. This is the 'developer's dilemma'. This study analyses the dilemma as it manifested itself in the Indian context, and identifies two distinct episodes over the post-independence period. We characterize these two episodes as 'inclusion without growth' and 'growth without inclusion'. We argue that the trade-off in each of these episodes is explained by political factors and the economic ideology pertaining during this period, which in turn, drive the policy regimes and economic outcomes. We draw a few conclusions. First, economic ideology played an important role in driving structural transformation in India. Second, structural transformation did not lead to manufacturing-based industrialization in India due to increasing political competition. Third, the lack of manufacturing growth intensified the dilemma in the Indian context. Finally, we predict three alternative trajectories that structural transformation and inclusiveness may follow in this country.
Keywords: D31; O1; O14; P48; 330; developer's dilemma; India; inequality; Kuznets; policy; politics; structural transformation